(untitled) (Revista Justiça do Direito, 2016)
This article aims to verify the role of the main political institutions that directly deals with refugees in Brazil, from the action of the political centrality of the National Committee for Refugees and the Federal Police, through a literature review and interviews with border officers, under the Political Science. Decision-making processes, the bureaucratic procedures of migration control and security of the Brazilian government about the phenomenon of forced displacement of refugees seek to analyze the bureaucracy and procedural mechanisms geared to foreigners regarding refugees, by identifying the institutional difficulties, limits and challenges to the implementation of public policies geared to refugees. Highlighting the lack of coordination, fragmentation and pulverization of migration policy as a whole, and refugee policy in a particular way, connected with the authoritarian past of the country and the maintenance of restrictive mechanisms for local insertion of international migrants.